A toddler with a persisting limp after a minor trauma. Issue 3 (22nd October 2019) - Trombetta, Andrea; Conversano, Ester; Cozzi, Giorgio; Taddio, Andrea; Murru, Flora Maria; Barbi, Egidio
Abstract : : A 3-year-old toddler was admitted for a 5-day history of worsening painful limping on his left leg. History was remarkable only for a minor trauma 2 days before the onset of symptoms; the boy fell on his buttocks but was walking normally in the following days. No fever was reported. Pain was also present at night, with no response to oral ibuprofen. On physical examination, the patient refused to stand on his left leg, palpation of the left buttock evoked pain, and exorotation and abduction of the left hip were only moderately limited, without local signs of inflammation such as redness, swelling or skin warming. Blood tests showed elevated erythrocyte sedimentation rate (ESR) (98 mm/hour, normal value <20 mm/hour) with normal C reactive protein (CRP) level (0.5 mg/dL, normal value <0.5 mg/dL). His white cell count was 12 110 x 10 9 /L, haemoglobin was 127 g/L and PLT was 430 x 10 9 /L. Creatine kinase values were within the normal range. An X-ray of the pelvis was unremarkable. An ultrasound of the left hip showed a 2 mm articular effusion. Questions: Based on the clinical picture and laboratory tests, what is the most likely diagnosis? Perthes disease. Pyomyositis. Septic arthritis. Bone fracture. Leukaemia. What test could confirm the diagnosis? Bone scintigraphy. CT. Bone marrow aspirate. MRI. Intra-articular puncture. What is the mainstay of management of this condition? Wait and see. Surgical excision. Antibiotic course. Antineoplastic treatment. Answers can be found on page 2.